2022
DOI: 10.1152/japplphysiol.00175.2021
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in right ventricular adaptation to pressure overload in a rat model

Abstract: Sex differences in right ventricular mechanical efficiency and energetic adaptation to increased right ventricular afterload were measured. Despite sex-dependent differences in contractile and fibrotic responses, right ventricular mechanoenergetic adaptation was comparable between the sexes, suggesting a homeostatic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…However, a few studies over the past five years have raised the possibility that modulators other than sex hormones may also underlie the sexual dimorphism of RV remodeling. In a rat PAB model, ovary-intact and ovariectomized females had similar amounts of collagen content in the RV, 29 indicating that regulation of cardiac collagen content does not depend upon estrogen. Additionally, some sex chromosome-specific genes are associated with pathologic cardiac remodeling but not sex-hormone signaling.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, a few studies over the past five years have raised the possibility that modulators other than sex hormones may also underlie the sexual dimorphism of RV remodeling. In a rat PAB model, ovary-intact and ovariectomized females had similar amounts of collagen content in the RV, 29 indicating that regulation of cardiac collagen content does not depend upon estrogen. Additionally, some sex chromosome-specific genes are associated with pathologic cardiac remodeling but not sex-hormone signaling.…”
Section: Discussionmentioning
confidence: 86%
“…In these studies, ovariectomized adult female rodents developed worse disease progression, with more severe fibrosis and increased mortality, than those with intact ovaries. 28 Other studies of female rodents with and without ovariectomy have shown an estrogen-dependent anti-fibrotic signaling pathway in the pressure overloaded ventricle, 4, 6, 29, 30 though mechanistic details remain to be elucidated. Aside from sex hormone regulation of fibrosis, sex differences in cardiac fibroblasts (CFs) have also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Establishing a representative control cohort using sampling methodologies [ 45 ] probably would provide more robust comparisons between normotensive and PH model parameters. Lastly, it is well established that PH disproportionately affects women, with sex differences being a significant area of attention in the PH community [ 60 ]. Combining a larger, more diverse patient cohort in the parameter inference performed here may elucidate sex-dependent differences in right atrium, right ventricle and pulmonary artery, parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies have shown distinct differences in myocardial response to pressure overload, a common precursor of heart failure, in female and male animals [14][15][16] . Rat studies have shown that females typically exhibit diastolic dysfunction characterized by decreased compliance of the heart muscle, for which no mechanistic therapies have been established, and males more often develop systolic dysfunction with decreased ejection fraction and increased fibrosis, for which therapies have been established 17 . Heart failure itself also shows a sex-dependent divergence; HF with preserved ejection fraction, coupled with increased ventricular stiffness, is more common in women, whereas men are more afflicted by HF with reduced ejection fraction, leading to ventricular dilation 6 .…”
Section: Introductionmentioning
confidence: 99%